The effects of shell characteristics on the UV photoresponse behaviors of photoconductivity based on ZnO/ZnMgO core–shell nanowire arrays. (17th July 2015) - Fang, F; Wang, X J; Fang, X; Li, T; Wei, Zhipeng; Li, Jinhua; Chu, Xueying
Abstract: Through a facile hydrothermal process and atomic layer deposition (ALD) technology, we obtained a kind of ZnO/ZnMgO core–shell nanowire array. The x-ray diffraction (XRD) results show a dominant (002) peak appears in as-grown ZnO, while the strongest peak is assigned an intensity of (100) in ZnO/ZnMgO core–shell structure. After ZnMgO shell coating, the main ultraviolet emission peak in room photoluminescence (PL) spectrum splits into two peaks, which locate at 364 nm and 378 nm. Furthermore, significant enhancement (one order of magnitude) in photoconductivity has been demonstrated. It is possible that the ZnMgO layer acts as an interfacial carrier transport layer, reducing the probability of carrier recombination.